2016
DOI: 10.4314/afrrev.v10i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Determinants of Organizational Commitment and Employee Job Satisfaction

Abstract: The focus of this paper is on the identification of determinants of organizational commitment and employee job satisfaction. It is viewed as one of the basic concepts describing the relationship between an employee and an organization. In this paper determinants of organizational commitment, factors conditioning development of three organizational commitment components and various variables responsible for employee satisfaction is been discussed. These variables are: Organization development factors, Job secur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The people who counted career growth as their prime force for turnover have put a saddle on availability of opportunities and management relations as subprime forces, but they turnover for new venture for better wages or salary compensation. Osemeke (2016) focused their study on the identification of determinants of organizational commitment and employee job satisfaction. It was viewed as one of the basic concepts describing the relationship between an employee and an organization.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The people who counted career growth as their prime force for turnover have put a saddle on availability of opportunities and management relations as subprime forces, but they turnover for new venture for better wages or salary compensation. Osemeke (2016) focused their study on the identification of determinants of organizational commitment and employee job satisfaction. It was viewed as one of the basic concepts describing the relationship between an employee and an organization.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…This is possible when the reward system has brought about commitment in the employees. In the study of Osemeke (2016), it was identified that OC is greatly influenced by the type of reward that the employees receive. Also, employees' commitment to their organisation is enhanced by the use of a profit-sharing arrangement (Long, 2000;Osemeke, 2016), which is a system with the intent of returning to the employees a share of the fruits of their collective labour (Coyle-Shapiro, Morrow, Richardson, & Dunn, 2002).…”
Section: Reward and Performance Evaluation Criteriamentioning
confidence: 99%